2008
DOI: 10.1073/pnas.0806019105
|View full text |Cite
|
Sign up to set email alerts
|

RID1 , encoding a Cys2/His2-type zinc finger transcription factor, acts as a master switch from vegetative to floral development in rice

Abstract: Transition from the vegetative phase to reproductive phase is a crucial process in the life cycle of higher plants. Although the molecular mechanisms of flowering regulation have been extensively characterized in a number of plant species, little is known regarding how the transition process initiates. Here, we show that the Rice Indeterminate 1 (RID1) gene acts as the master switch for the transition from the vegetative to reproductive phase. RID1 encodes a Cys-2/His-2-type zinc finger transcription factor th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
193
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(207 citation statements)
references
References 41 publications
10
193
1
3
Order By: Relevance
“…In LD conditions, the expression of Hd3a is suppressed by Hd1 (Hayama et al, 2003), and Ehd1 and Hd3a are also suppressed by Ghd7 (Xue et al, 2008), which accounts for the late flowering in rice. Additionally, RID1/OsID1/Ehd2 promotes flowering under both SD and LD conditions by up-regulating Ehd1 (Matsubara et al, 2008;Park et al, 2008;Wu et al, 2008). In this study, DTH8 was found to delay rice flowering time by negatively influencing the expression of Ehd1 and Hd3a in LD conditions ( Fig.…”
Section: Dth8 Is a Novel Flowering Suppressormentioning
confidence: 49%
See 3 more Smart Citations
“…In LD conditions, the expression of Hd3a is suppressed by Hd1 (Hayama et al, 2003), and Ehd1 and Hd3a are also suppressed by Ghd7 (Xue et al, 2008), which accounts for the late flowering in rice. Additionally, RID1/OsID1/Ehd2 promotes flowering under both SD and LD conditions by up-regulating Ehd1 (Matsubara et al, 2008;Park et al, 2008;Wu et al, 2008). In this study, DTH8 was found to delay rice flowering time by negatively influencing the expression of Ehd1 and Hd3a in LD conditions ( Fig.…”
Section: Dth8 Is a Novel Flowering Suppressormentioning
confidence: 49%
“…More genes for plant height in rice have been identified (Ashikari et al, 1999;Yamamuroa et al, 2000;Sasaki et al, 2002Sasaki et al, , 2003Honga et al, 2003;Itoh et al, 2004;Tanabe et al, 2005). The molecular genetic pathway for flowering time has been under elucidation in rice since the isolation of many correlative genes or QTLs (Yano et al, 2000;Kojima et al, 2002;Doi et al, 2004;Kim et al, 2007;Wu et al, 2008). Although there are close correlations among yield, plant height, and flowering time, most of these genes were reported to be regulating only one of the three traits.…”
Section: Dth8 Has Pleiotropic Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been known for centuries that flowering of plants is regulated by day length (2). In recent years, many genes for photoperiod-controlled flowering have been identified in a number of plants, leading to characterization of pathways in flowering regulation (3)(4)(5)(6)(7)(8)(9). However, photoperiod regulation of other developmental processes has been studied in far less detail than flowering.…”
mentioning
confidence: 99%